2018
DOI: 10.1002/anie.201812244
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective α‐Ketol Rearrangement

Abstract: Ahighly enantioselective a-ketol rearrangement has been developed. In the presence of ac hiral Cu-bisoxazoline complex, achiral b-hydroxy-a-dicarbonyls were isomerized to chiral a-hydroxy-b-dicarbonyls and their bicyclic derivatives in excellent yields and enantioselectivities.E nantioenriched 2-acyl-2-hydroxy cyclohexan-1-ones,d ihydroxyhexahydrobenzofuranones,a nd dihydroxyhexahydro-cycloheptafuranones,w ith up to three stereocenters,w ere readily prepared from achiral starting materials in one operation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Important examples include the industrial processes for the carbonylation of methanol to produce acetic acid catalyzed by rhodium (the Monsanto process), and iridium (the Cativa process) [13–15] . Additionally, the acyl migration process represents an essential tool for the construction of complex molecules [16–21] …”
Section: Methodsmentioning
confidence: 99%
“…Important examples include the industrial processes for the carbonylation of methanol to produce acetic acid catalyzed by rhodium (the Monsanto process), and iridium (the Cativa process) [13–15] . Additionally, the acyl migration process represents an essential tool for the construction of complex molecules [16–21] …”
Section: Methodsmentioning
confidence: 99%
“…The α-ketol rearrangement, also called acyloin rearrangement, transforms the α-hydroxy aldehydes/ketones to their constitutional isomers via a 1,2-alkyl­(aryl) migration (Scheme a). The reaction takes place reversibly under acidic, basic, or thermal conditions leading to the thermodynamically more stable isomer. It has been exploited in total synthesis and structural modification of natural products and is involved in the biosynthesis of several classes of natural products.…”
Section: 2-shift In Domino Processesmentioning
confidence: 99%
“…In a similar investigation except with copper(II) as the metal and β-hydroxy-α-diketone 6 as the substrate, the catalyst containing the chiral bisoxazoline ligand ( S , S )- 8 led to the α-ketol rearrangement product 7 in 70% yield and 68% ee ( Figure 3 ) [ 5 ]. The study further demonstrated the effectiveness of the catalyst for a series of analogues of 6 bearing various replacements for the phenyl group, often proceeding with greater than 80% ee.…”
Section: Reviewmentioning
confidence: 99%